2017
DOI: 10.1089/jpm.2017.0143
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Palliative Care Intervention into Community Practice for Lung Cancer: A Study Protocol and Lessons Learned with Implementation

Abstract: Efforts to disseminate and implement previously tested PC models into real-world community practices need to be more realistic and consider the local context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The TLC-PC intervention was adapted from earlier work at City of Hope 4,5 and described recently. 2 The PC intervention consisted of three key components: comprehensive patient/FCG assessment using standardized study measures, interdisciplinary care planning, and patient/FCG education. The first component involved a comprehensive baseline assessment of the patient’s and caregiver’s QOL followed by the development of an individualized interdisciplinary care plan based on patient’s and FCG’s concerns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLC-PC intervention was adapted from earlier work at City of Hope 4,5 and described recently. 2 The PC intervention consisted of three key components: comprehensive patient/FCG assessment using standardized study measures, interdisciplinary care planning, and patient/FCG education. The first component involved a comprehensive baseline assessment of the patient’s and caregiver’s QOL followed by the development of an individualized interdisciplinary care plan based on patient’s and FCG’s concerns.…”
Section: Methodsmentioning
confidence: 99%
“…We recently described the protocol for the Translation of a Lung Cancer Palliative Care Intervention (TLC-PCI) study and lessons learned from adapting and implementing the PC intervention at three sites in a large integrated health care system (Kaiser Permanente Southern California (KPSC)). 2…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, detailed attention to planning is needed for introducing palliative care into varied settings. A recent study implementing palliative care into a real-world community practice identified the need to adapt palliative care support to the existing work settings [ 63 ]. To support sustainability, assessment tools, planning forms and educational programmes need to be tested in the actual practice settings to decrease patient and caregiver burden and truly integrate the palliative care team into the system of care.…”
Section: Palliative Care Symptom Management For Patients With Respiramentioning
confidence: 99%
“…Since adoption of PC services is subject to variance across the sites, this variability in implementation provided an opportunity for the PCI model to be adopted, and if successful would be disseminated to the remaining sites within the healthcare system. 18 This healthcare system was chosen for its substantial commitment of bridging outpatients services to the community and to include diverse populations. This PCI was previously developed and tested at a National Cancer Institute (NCI)-designated comprehensive cancer center.…”
Section: Methodsmentioning
confidence: 99%
“…16 The study protocol and lessons learned were previously discussed, which included the facilitators and barrier to implementation. 18 This study describes the perspectives of PC and oncology clinicians as they prepared to implement this structured nurse-led PCI for NSCLC patients and their primary FCGs in community based settings.…”
Section: Methodsmentioning
confidence: 99%